Increasing access to housing in an economy of disparity - the role of civil society. - Mann, Chantal (My University, 2010)
The significant dearth of adequate housing in South Africa juxtaposed against the vast wealth held captive by small portion of the population forms the backdrop to this research. This study investigates the state of civil society activism in South Africa’s housing sector. This research questions if the civil society contribution to the assisted housing sector in South Africa is operating at an appropriate and effective level and asks what has enabled this; and what are the inhibiting factors that prevent civil society activism from flourishing in assisted housing? Through conduct of a field study which solicits data from State Department of Human Settlement leaders and Civil Society housing activists, this research probes interrelationships between key stakeholders in the sector and determines the space for, and ways in which, civil society is contributing to housing and the challenges it faces. Obstacles preventing civil society activism in the housing sector from flourishing were identified through this study. At the state level these include attitudes of paternalism, the prioritization of attainment of housing targets at the expense of participatory processes, and a disconnect between policy and practice at state level. Diminishing human and fiscal capacity within civil society and threats from amongst state and civil society superstructures were also determined to be a factors restricting civic performance in this sector. This research provides evidence to suggest that civil society contributions to the housing sector are weak. State housing polices and acts were found to support participatory development but fractures in these mechanisms identified in this study prevent the two main stakeholders (state and civil society) from synergising effectively to extract their best resources and inputs from being realised.